2008
DOI: 10.1111/j.1440-1746.2008.05321.x
|View full text |Cite
|
Sign up to set email alerts
|

Virological and clinical implication of core promoter C1752/V1753 and T1764/G1766 mutations in hepatitis B virus genotype D infection in Mongolia

Abstract: In Mongolians infected with HBV/D, C1752 and/or V1753 mutation was associated with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
(98 reference statements)
7
22
1
Order By: Relevance
“…In Mongolia and Inner Mongolia, which are located in the north of Gansu and Ningxia provinces, genotype D is the most prevalent HBV strain, and ‘CD1’ recombinant was observed with a very low prevalence [24], [25], [26]. In contrast, we found that ‘CD2’ exists at a slight higher prevalence than ‘CD1’ in Tibet, contradicting a previous prediction that all C/D hybrids were ‘CD2’ recombinant in this region [16].…”
Section: Discussioncontrasting
confidence: 99%
“…In Mongolia and Inner Mongolia, which are located in the north of Gansu and Ningxia provinces, genotype D is the most prevalent HBV strain, and ‘CD1’ recombinant was observed with a very low prevalence [24], [25], [26]. In contrast, we found that ‘CD2’ exists at a slight higher prevalence than ‘CD1’ in Tibet, contradicting a previous prediction that all C/D hybrids were ‘CD2’ recombinant in this region [16].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, 93.2% of genotype D strains had pre-C stop codon G1896A mutation, whereas only four genotype A2 strains had this mutation. This result was consistent with previous data showing that G1896A mutation was the strongest factor of HBeAg clearance in HBV/D-infected individuals [38], [39]. The basis of the relation between G1896A mutation and HBV genotypes is due to the base pairing of the stem loop structure of the encapsidation signal (ε), essential for viral replication.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the relationship between this mutation and severity of liver disease is not mediated by an increase in HBV replication but probably to direct pathogenic or oncogenic effects of this mutation. The T1753V mutation had earlier been associated with HCC development among Mongolian patients with genotype D [39]. Regarding the biological aspects, it was suggested that T1753V lead to the enhancement of transactivation and antiproliferation activity of HBx protein by altering HBx aa 127 (I127T/N/S) and enhancement of virus replication leading to persistent infection and higher frequency of HBV-DNA integration events into the human genome [52].…”
Section: Discussionmentioning
confidence: 99%
“…1 HBsAg endemicity in 1990-2013 and geographic distribution of HBV genotypes in Asia. The prevalence data are retrieved from a systematic review [1]; this map is prepared according to the literature [1,6,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] HBV genotypes and response to antiviral therapy in Asia HBV genotypes and response to interferon (IFN)-based therapies HBV genotypes are significantly associated with sustained response to IFN-based therapies. In general, for HBeAgpositive patients, the probability of sustained response is in a descending order from genotype A-D [50].…”
Section: Hbv Genotypes and Clinical Manifestation In Asiamentioning
confidence: 99%